Junior Science for General Education - Sarno, Filomena (My University, 2013)
The focus of this project is the development of a unit of study in Science for junior students (ages 9-11), in the Elementary School and the assessment of its implementation. The actual participants in the programme were students at the grade five level.
There are two areas of student learning that have been identified as significant in science education: the cognitive-process skills, and the communicative skills. Through application and assessment of the proposed programme, "Junior Science For General Education", it was discovered that active "hands-on" participation resulted in an increased capacity for problem solving.
Keywords: Science; Science and Mathematics Education; Science and Mathematics Education